Kesulitan Keuangan Terkait Manajemen Laba dengan Fraud Hexagon sebagai Variabel Moderasi - Muhammad Khalid Azka; Agustina Mappadang; Isti Pajar Agustiani (Penerbit Goodwood, 2025)
Purpose: To empirically test and analyze the influence of a company's Financial Distress condition on Earnings Management, and to empirically test and analyze the influence of a company's Financial Distress condition on Earnings Management based on Fraud Hexagon. Research/Methodology: Secondary data, banking financial report data, statistical analysis, quantitative methods with descriptive analysis and hypothesis testing, Warppls 7.0, evaluation of structural models and goodness of fit, collection of banking financial report data on the Indonesian stock exchange. Results: In this research, the Financial Distress variable cannot affect the practice of Earnings Management in a company and Fraud Hexagon cannot moderate the influence of Financial Distress on (Earnings Management). Conclusions: The presence of fraudulent elements can exacerbate the challenges faced by a company during financial distress, thereby potentially increasing the risk of fraudulent activities and unethical behavior in financial reporting. Limitations: This study is limited by small sample size, inadequate data quality, and the influence of unexpected external factors, so the results may not be widely generalizable. Contribution: Provides new insights into the relationship between financial distress and earnings management, has practical implications for improving financial transparency, and provides policy recommendations for tightening regulations to prevent fraud in financial reporting.